Battery and electric device
By adjusting the silicon content, electrolyte viscosity and separator coating thickness in the negative electrode active material layer, ensuring that the value of a*b/c is within a specific range, the problem of deterioration of battery fast charging performance is solved and better electrolysis is achieved Liquid infiltration and battery performance.
Patent Information
- Application Number
- CN202411600580.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
AI Technical Summary
After the silicon content of existing batteries in the negative electrode increases, the battery fast charging performance becomes worse.
By adjusting the mass percentage of silicon elements in the negative active material layer, the viscosity of the electrolyte, and the percentage of the membrane coating thickness and the membrane thickness, the value of a*b/c is ensured to be within the range of 0.037-5.625 to improve the electrolyte pair The wetting effect of the negative electrode and the fast charging performance of the battery.
It effectively improves the wetting effect of the electrolyte on the negative electrode and the fast charging performance of the battery, taking into account the energy density and circulation performance of the battery.
Smart Images

Figure BDA0005128198210000131 
Figure BDA0005128198210000141 
Figure BDA0005128198210000171
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to a battery and an electrical device. Background Art
[0002] A lithium battery includes a battery cell consisting of a positive electrode, a negative electrode and a separator, an electrolyte filled in the battery cell, and a battery casing that wraps the battery cell and the electrolyte; the negative electrode of a conventional battery consists of a current collector and a negative electrode active material layer coated on the current collector.
[0003] Among them, the negative electrode active material in the negative electrode active material layer conventionally uses graphite or carbon with a structure similar to graphite, and in order to increase the energy density of the battery, silicon can be doped in the conventional negative electrode active material layer. However, when the silicon content in the negative electrode increases, it will lead to increased expansion of the negative electrode, poor electrolyte infiltration effect, and poor battery fast charging performance. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect of the battery disclosed in the prior art that the fast charging performance of the battery deteriorates after the silicon content in the negative electrode increases, thereby providing a battery and an electrical device that solve the above problem.
[0005] To achieve the above-mentioned purpose, the present invention provides a battery, comprising a battery cell and an electrolyte, the battery cell comprising a negative electrode and a separator, the negative electrode comprising a current collector and a negative electrode active material layer, the negative electrode active material layer comprising a silicon-based material, and the separator comprising a base film and a coating; the mass percentage of silicon element in the negative electrode active material layer is a; the viscosity of the electrolyte is b cp; the percentage of the thickness of the coating and the separator is c; 0.037≤a*b / c≤5.625.
[0006] The present invention also provides an electrical device, comprising the electrochemical device mentioned above.
[0007] The beneficial effects of the present invention are:
[0008] The present invention adjusts the mass percentage a of silicon element in the negative electrode active material layer, the electrolyte viscosity b cp and the percentage c of coating thickness / diaphragm thickness, and comprehensively controls the value of a*b / c within the range of 0.037-5.625, thereby improving the wetting effect of the electrolyte on the negative electrode and the fast charging performance of the battery. DETAILED DESCRIPTION
[0009] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0010] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0011] The "range" disclosed in the present invention is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 50%-90% and 60%-80% is listed for a particular parameter, it is understood that the range of 50% to 80% and 60% to 90% is also expected.
[0012] A battery includes a battery cell and an electrolyte, wherein the battery cell includes a negative electrode sheet and a separator, the negative electrode sheet includes a current collector and a negative electrode active material layer, the negative electrode active material layer includes a silicon-based material, and the separator includes a base film and a coating; the mass percentage of silicon element in the negative electrode active material layer is a; the viscosity of the electrolyte is b cp; the percentage of the coating thickness to the separator thickness is c; 0.037≤a*b / c≤5.625. That is, the value of a*b / c is any value between 0.037-5.625, for example: 0.037, 0.05, 0.1, 0.15, 0.2, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.625, etc.
[0013] The present invention can improve the electrolyte wetting effect on the negative electrode and the fast charging performance of the battery by adjusting the silicon content a, the electrolyte viscosity b cp and the percentage of coating thickness / diaphragm thickness c%, and comprehensively controlling the value of a*b / c within the range of 0.037-5.625. Among them, during the battery charging and discharging process, the silicon content is high, the volume of the active material layer expands greatly during the battery charging or discharging process, and the pores inside the pole piece increase. The pores need to be filled with electrolyte. If the electrolyte viscosity is relatively high, it will cause poor pole piece wetting effect, which is not conducive to lithium ion transmission and poor fast charging performance. Therefore, a lower electrolyte viscosity is required to quickly and fully fill the pores and then infiltrate the negative electrode; therefore, when the silicon content is high, the electrolyte viscosity b cp should not be too large; in addition, the coating of the diaphragm has a certain ability to retain liquid. When the electrode expands, the diaphragm is squeezed, and the electrolyte in the diaphragm is squeezed out. During the expansion of the negative electrode, more pores can absorb the electrolyte squeezed out of the diaphragm, so that the electrolyte can enter the electrode; therefore, the thickness of the coating in the diaphragm cannot be too small, that is, the percentage c of the coating thickness / diaphragm thickness cannot be too small; at the same time, the viscosity of the electrolyte cannot be too low. The electrolyte includes solvents and solutes. The greater the viscosity, the stronger the interaction between the solute and the solvent, and the lower the viscosity, the greater the interaction between the solvent and the solute. The weaker it is, the lower the viscosity is, which will cause the solute transfer rate and the solvent transfer rate to be inconsistent, which will lead to a serious mismatch between the solvent and solute transfer rates, and will cause the wetting ability of the electrode to deteriorate; in addition, the thickness of the coating in the diaphragm cannot be too thick. Generally, the amount of battery injection is certain. When the thickness of the coating in the diaphragm is relatively large, the electrolyte content absorbed by the diaphragm is high, and the amount of electrolyte left for the electrode is relatively small. Although the subsequent charging expansion of the diaphragm electrolyte can release part of it to the negative electrode, it will also cause a small amount of electrolyte on the negative electrode side at the beginning. In summary, the present invention comprehensively controls the mass percentage a of the silicon element in the negative electrode active material layer, the viscosity b of the electrolyte, and the percentage c of the coating thickness to the diaphragm thickness, so that 0.037≤a*b / c≤5.625, which effectively improves the wetting of the negative electrode sheet and thus improves the fast charging performance of the battery.
[0014] Adding silicon to the negative electrode active material can improve the battery energy density. The silicon in the negative electrode active material layer can come from silicon-carbon material and / or silicon-oxygen material. The silicon content refers to the mass percentage a of silicon in the negative electrode active material layer, and the silicon content a is controlled to be 0.5%-30%. For example, a is controlled to be 0.5%, 1%, 2%, 3%, 5%, 10%, 15%, 20%, 25%, 30%, etc.
[0015] In a preferred embodiment, the content a of silicon in the negative electrode active material layer is preferably controlled to be 2%-16%; specifically, in the present invention, a negative electrode sheet with a higher silicon content is preferred, which can improve the energy density of the battery; however, the silicon content cannot be too high, which will cause the negative electrode sheet to expand more, resulting in increased pores in the electrode sheet and increased demand for electrolyte to wet the electrode sheet. Therefore, the content a of silicon in the negative electrode active material layer of the present invention is preferably controlled to be 2%-16%.
[0016] The viscosity b of the electrolyte affects the wetting effect of the electrolyte. The viscosity of the electrolyte in the present invention is controlled within the range of 1.5-3.7 cp; for example: b is controlled to be 1.5, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.7, etc.
[0017] In a preferred embodiment, the viscosity of the electrolyte is preferably controlled within the range of 2.1-2.8cp; specifically, in the present invention, an electrolyte with a lower viscosity is preferred, which can improve the fluidity of the electrolyte and enhance the wetting effect of the electrolyte on the electrode, but the viscosity of the electrolyte cannot be too low. If it is too low, it will cause a serious mismatch between the solvent and solute transmission rates in the electrolyte, which will in turn cause the wetting ability to the electrode to deteriorate; therefore, the viscosity of the electrolyte is preferably controlled within the range of 2.1-2.8cp to improve the wetting effect of the electrolyte on the electrode.
[0018] The diaphragm includes a base film and a coating, and the coating is arranged on the surface of the base film; the coating generally includes an inorganic component and an organic component; the coating has a porous structure and has liquid absorption capacity, and the liquid absorption capacity of the coating is related to the thickness of the coating; the liquid absorption capacity of the diaphragm can be adjusted by controlling the percentage c of the coating thickness and the diaphragm thickness; in the present invention, the percentage c of the coating thickness and the diaphragm thickness can be controlled to be 8%-50%; for example: controlling the c to be 8%, 10%, 12%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc.
[0019] In a preferred embodiment, the percentage c of coating thickness / diaphragm thickness is preferably controlled within the range of 13%-32%; specifically, in the present invention, a setting of coating thickness / diaphragm thickness with a higher percentage c is preferred to improve the coating's liquid absorption capacity; but the percentage c of coating thickness / diaphragm thickness cannot be too high. When it is too high, the coating's liquid absorption capacity will be too large. When the electrolyte injection amount is certain, most of the electrolyte will be absorbed by the diaphragm, resulting in a decrease in the amount of electrolyte absorbed by the negative electrode sheet at the beginning, a poor lithium ion transmission rate, and poor battery fast charging performance; therefore, the present invention preferably controls the c to 13%-32%, which is more conducive to a more appropriate amount of electrolyte in the diaphragm, which can be released and infiltrated into the electrode sheet during the subsequent electrode sheet expansion process.
[0020] Furthermore, by controlling the value of a*b / c within a more preferred range, the negative electrode wettability and fast charging performance of the present invention are better. For example, the value of a*b / c is controlled to be between 0.165-2.585.
[0021] When the silicon-based material includes a silicon-carbon material, the silicon-carbon material includes a porous carbon matrix and silicon particles. The silicon particles are pure silicon grains. The silicon particles are embedded in the porous carbon matrix. The porous carbon can use its own pores to alleviate expansion, the expansion of the electrode is reduced, the viscosity of the electrolyte can be appropriately increased, and the amount of electrolyte absorbed by the diaphragm can also be appropriately reduced; therefore, the value of a*b / c is preferably 0.431-1.05.
[0022] The energy density of the battery is related to the compaction density of the negative electrode sheet. When the compaction density is appropriately increased, the contact between particles can be improved, the electronic conductivity of the negative electrode sheet can be improved, and the energy density of the battery can be improved. In the present invention, the compaction density of the negative electrode is 1.25-1.8g / cm 3 ; For example: 1.25g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 wait.
[0023] The increase in compaction density is beneficial to improving the energy density of the battery; however, after the compaction density is higher, the pores of the pole piece become smaller, and the amount of electrolyte that can be initially stored in the pole piece is small, which can reduce the viscosity b of the electrolyte and further control the range of a*b / c so that the pores are fully infiltrated with electrolyte; in addition, the relationship of the coating thickness / diaphragm thickness percentage c can be appropriately increased to increase the liquid retention of the diaphragm, so that the electrolyte in the subsequent diaphragm is squeezed out and then reversely infiltrates the pole piece; specifically, when the negative electrode compaction density is 1.45-1.8g / cm 3 When the value of a*b / c is preferably 0.333-0.820, the negative electrode wetting and fast charging performance are better.
[0024] The electrolyte includes a solvent and a lithium salt;
[0025] The solvent is selected from carbonates, carboxylates, ethers, sulfones, nitriles, phosphates or fluorides of the above solvents;
[0026] The lithium salt is selected from lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium perchlorate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(trifluoromethanesulfonyl imide), lithium difluorobis(oxalatophosphate) and lithium tetrafluorooxalatophosphate.
[0027] In order to reduce the viscosity of the electrolyte, the solvent contains at least 10% to 60% of a carbonate solvent and 0% to 50% of a carboxylate solvent;
[0028] And / or, the lithium salt concentration in the electrolyte is 0.8-2.5M; for example: 0.8M, 0.9M, 1.0M, 1.2M, 1.5M, 1.8M, 2.0M, 2.3M, 2.5M.
[0029] For the diaphragm, the coating contains inorganic components and has good liquid retention capacity; wherein, the coating thickness cannot be too large, if the coating thickness is too large, the diaphragm absorbs a large amount of electrolyte, most of the electrolyte is absorbed by the diaphragm, and the amount of electrolyte that can be supplied to the negative electrode becomes less; at the same time, the coating thickness cannot be too small, the coating has a certain liquid retention capacity, which can be used to properly supplement the negative electrode electrolyte in the subsequent long cycle process; therefore, the thickness of the coating is preferably 1-7μm; for example: 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, etc.
[0030] The inorganic component contained in the coating is selected from alumina, boehmite, silica, zirconia, titania, cerium oxide, magnesium aluminate and the like.
[0031] An electrical device, comprising the above-mentioned battery; the battery comprises a positive electrode sheet, wherein the positive electrode active material in the positive electrode sheet comprises LiNi x Co y Mn z O2, where 1>x≥0.5, x+y+z=1.
[0032] The following detailed description specifically discloses the embodiments of the battery and the electrical device of the present invention. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the following description is provided for those skilled in the art to fully understand the present application and is not intended to limit the subject matter described in the claims.
[0033] [Battery]
[0034] The battery of the present invention is a secondary battery, also known as a rechargeable battery or storage battery, which refers to a battery that can be continuously used by activating the active material by charging after the battery is discharged.
[0035] Typically, a battery includes a cell, an electrolyte, and an outer packaging shell; a cell includes a positive electrode, a negative electrode, and a separator. During the battery charge and discharge process, active ions (such as lithium ions) are embedded and removed back and forth between the positive electrode and the negative electrode. The separator is set between the positive electrode and the negative electrode, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing active ions to pass through. The electrolyte is between the positive electrode and the negative electrode, mainly to conduct active ions.
[0036] As an example, the preparation process of the battery is: stack the positive electrode sheet, the separator, and the negative electrode sheet in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then wind them to obtain a bare battery cell; place the bare battery cell in an outer packaging shell, inject electrolyte after drying, and obtain a secondary battery through vacuum packaging, standing, formation, shaping and other processes.
[0037] [Positive electrode]
[0038] The positive electrode sheet generally includes a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector. The positive electrode film layer includes a positive electrode active material, a conductive agent, and a binder. The positive electrode active material may be any commonly used positive electrode material.
[0039] The preparation method of the above-mentioned positive electrode sheet is: disperse the positive electrode active material, conductive agent, binder and any other components in a solvent, stir until the system is uniform under the action of a vacuum mixer, and obtain a positive electrode slurry; evenly coat the positive electrode slurry on both surfaces of the positive electrode current collector aluminum foil, dry it at room temperature, transfer it to an oven for further drying, and then obtain a positive electrode sheet by cold pressing and slitting.
[0040] In the present invention, the positive electrode active material is a conventional positive electrode active material in the battery field, for example: a ternary positive electrode material LiNi x Co y Mn z O2, etc., where 1>x≥0.5, x+y+z=1.
[0041] The conductive agent is used to improve the conductivity between the positive electrode active material particles. In the present invention, the conductive agent can be a conventional choice in the battery field, such as carbon nanotubes, carbon black or graphene.
[0042] The binder is used to improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. In the present invention, the binder can be a conventional choice in the battery field. For example, the binder can be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyolefin, sodium carboxymethyl cellulose (CMC) or sodium alginate.
[0043] The solvent of the present invention is used to achieve uniform dispersion among the positive electrode active material, the conductive agent and the binder, and can be a conventional solvent type in the battery field, such as: NN dimethylacetamide, dimethyl sulfoxide, trimethyl phosphate, dimethyl carbonate, NN dimethylformamide, etc.
[0044] The present invention has no particular limitation on the positive electrode current collector as long as it has conductivity and does not cause adverse chemical changes in the battery, and can use, for example: stainless steel, aluminum, nickel, titanium, fired carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc.
[0045] [Negative electrode]
[0046] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer arranged on at least one side of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes conventional silicon-based materials and other negative electrode active materials in the battery field; the silicon-based material includes silicon-carbon material and / or silicon-oxygen material; other negative electrode active materials include: artificial graphite, natural graphite, etc.
[0047] The present application does not limit the preparation method of silicon-carbon material. Specifically, it can be prepared by chemical vapor deposition (CVD deposition method); specifically, by porous carbon adsorption, silane is gradually decomposed at 450-500°C to produce silicon element, and deposited into the carbon skeleton; acetylene carbon coating (500-550°C) forms a stable coating carbon layer on the silicon-carbon surface, and finally obtains silicon-carbon material, which will not be repeated here. The present invention can control the number of silicon particles deposited in porous carbon by controlling the silane flow rate and deposition time.
[0048] In some embodiments, the conductive agent is used to improve the conductivity between the negative electrode active material particles. The negative electrode active material layer may also optionally include a conductive agent. In the present invention, the conductive agent may be a conventional choice in the battery field. As an example, the conductive agent may be selected from carbon nanotubes, carbon black or graphene.
[0049] The binder is used to improve the adhesion between the negative electrode active material particles and the adhesion between the negative electrode active material and the current collector. In the present invention, the binder can be a conventional choice in the battery field. For example, the binder can be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyolefin, sodium carboxymethyl cellulose (CMC) or sodium alginate.
[0050] In some embodiments, as an example, the negative electrode current collector is a copper foil.
[0051] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, rolling, cutting and other processes, the negative electrode sheet can be obtained.
[0052] [Electrolyte]
[0053] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The electrolyte includes a solvent and a solute. The present invention has no specific restrictions on the type of solute of the electrolyte, and it can be selected according to needs. As an example, the electrolyte of the present invention can be various electrolytes suitable for electrochemical energy storage devices in the art. The solute generally includes a lithium salt, and the solvent is an organic solvent.
[0054] Specifically, the lithium salt concentration in the electrolyte is 0.8-2.5M, and the lithium salt is selected from at least one of lithium hexafluorophosphate (LiPF6), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium trifluoromethanesulfonate (LiTFS), lithium bis(fluorosulfonyl imide) (LiFSI), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0055] Specifically, the solvent is selected from carbonates, carboxylates, ethers, sulfones, nitriles, phosphates or fluorides of the above solvents; the solvent contains at least 10% to 60% of carbonate solvents and 0% to 50% of carboxylate solvents. For example, the solvent includes at least one of fluoroethylene carbonate (FEC), propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl propionate (EP), ethyl acetate (EA), acetonitrile (AN), and trifluoroethanol (TFEA).
[0056] [Diaphragm]
[0057] The present invention uses a separator having a base film and a coating layer.
[0058] The present invention has no particular limitation on the type of base film, and any known porous base film with good chemical stability and mechanical stability can be selected; in some embodiments, as an example, the base film is one of PP or PE.
[0059] The coating in the present invention includes an inorganic component; the inorganic component is selected from alumina, boehmite, silica, zirconium oxide, titanium dioxide, cerium oxide and magnesium aluminate, etc.; in some embodiments, it also includes an organic component, which is selected from polyvinylidene fluoride, polymethyl methacrylate, aramid, etc.
[0060] Example 1
[0061] A battery comprises a battery cell and an electrolyte, wherein the battery cell comprises a negative electrode and a separator, the negative electrode comprises a current collector and a negative electrode active material layer, the negative electrode active material layer comprises a negative electrode active material, the negative electrode active material comprises a silicon-based material, and the silicon-based material is a silicon-carbon material, and the separator comprises a base film and a coating.
[0062] 1. Preparation of positive electrode
[0063] The specific preparation process of the positive electrode sheet is as follows: the positive electrode active material LiNi x Co y Mn z O2 (x=0.92, y=0.05, z=0.03), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 92:4:4, solvent NMP is added, and the mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on both surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0064] 2. Preparation of negative electrode sheet
[0065] The specific preparation process is as follows: the negative electrode active material, the conductive agent carbon black, the thickener CMC, and the binder SBR are mixed in a mass ratio of 96.4:1:1.2:1.4, and the solvent deionized water is added, and the mixture is stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the negative electrode current collector copper foil, and after drying at room temperature, it is transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet. After cold pressing, a negative electrode sheet with a compaction density as shown in Table 1 is obtained. The compaction density of the negative electrode sheet in this embodiment is 1.6 g / cm 3 .
[0066] In the present invention, the negative electrode active material is obtained by mixing artificial graphite and silicon-carbon material in a mass ratio of (40-99): (1-60). In this embodiment, the artificial graphite and silicon-carbon material are mixed in a mass ratio of 65.2: 34.8 in Table 1; wherein, the silicon-carbon material is prepared by chemical vapor deposition (CVD deposition); specifically, through the porous carbon adsorption force, at a deposition temperature of 450°C, silane is decomposed at high temperature to produce gaseous silicon and hydrogen, wherein the gaseous silicon will be deposited in the carbon matrix, that is, the gaseous silicon is gradually infiltrated into the carbon skeleton under this condition; after the silicon matrix is deposited, a carbon coating layer is required to prevent pure silicon from contacting the air; that is, acetylene carbon is coated on the silicon-carbon surface under a carbon coating temperature of 550°C to form a stable silicon-carbon material. In the preparation of the silicon-carbon material of the present invention, the synchronous deposition process of silane decomposition occurs at high temperature, the silane flow rate is controlled to be 18L / min, and the deposition time is controlled to be 15h, and a silicon-carbon material with a silicon content of 50% is prepared.
[0067] 3. Obtaining the diaphragm
[0068] The diaphragm in this embodiment is a commercially available product, which includes a base film and a coating. The parameters of the diaphragm are shown in Table 1. In the diaphragm in this embodiment, the base film is made of PP, the base film thickness is 12 mm, the inorganic component in the coating is aluminum oxide, and the coating thickness is 1.5 mm.
[0069] 4. Preparation of electrolyte
[0070] The specific preparation process is: various solvents are mixed in a glove box filled with argon to obtain an organic solvent. In this embodiment, fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), and propylene carbonate (PC) are mixed in a mass ratio of 15:20:60:5, and then the fully dried lithium salt (LiPF6) is dissolved in the mixed organic solvent, followed by adding 0.5% 1,3-propane sultone, 0.5% tris(trimethylsilyl) phosphate, and 1% vinyl sulfate to the electrolyte, and stirring until completely dissolved to prepare an electrolyte with a lithium salt concentration of 2.5M corresponding to Table 1.
[0071] 5. Battery assembly
[0072] The specific process is: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then wind them to obtain a bare battery cell; place the bare battery cell in an outer packaging shell, inject electrolyte after drying, and obtain a lithium-ion battery through vacuum packaging, standing, formation, constant capacity and other processes.
[0073] Examples 2-12 and Comparative Examples 1-2
[0074] A secondary battery, which is different from Example 1 in that the parameters and conditions in the preparation of the negative electrode sheet, the acquisition of the diaphragm and the preparation of the electrolyte are different, and the different parameters are shown in Table 1 below. The others are exactly the same as Example 1.
[0075] Table 1
[0076]
[0077]
[0078] The batteries of the above-mentioned embodiments and comparative examples were subjected to tests a, b and c.
[0079] Detection of a: that is, the detection of the mass percentage a of silicon element in the negative electrode active material layer. The detection process is as follows:
[0080] Pretreatment: Use DMC solvent to clean the negative electrode sheet, dry it at 60℃ and then scrape off the powder.
[0081] Weigh the sample, place it in a nickel crucible pre-filled with potassium hydroxide, add a little potassium hydroxide to cover the surface of the sample, drip two drops of ethanol, place it on an electric furnace and heat it until the potassium hydroxide melts and dehydrates, then move it to a muffle furnace at 1100°C, keep it molten and keep warm for 8 hours, take out the nickel crucible, and cool it slightly. Put the crucible together in a 300mL plastic beaker, add hot water for extraction, take out the crucible after the reaction, add HCl to the beaker for acidification, add hydrogen peroxide, filter out other impurities after cooling, transfer the filtered solution to a 100mL volumetric flask, make up to volume, and shake well. After standing, take the solution into another 100mL volumetric flask, make up to volume, shake well, stand to clarify, and wait for testing. At the same time, prepare a blank solution, which means that no sample is added, and then follow the above steps to obtain a solution. Then, according to the characteristics of the sample and the elements to be detected, appropriate ICP instrument working conditions were set, including a gas flow rate of 0.5L / min, a power of 1150W, and a Si element determination wavelength of 288.158nm; and the Si content of the element was tested by ICP.
[0082] Detection of b: that is, the detection of the viscosity b of the electrolyte. The detection process is as follows:
[0083] The battery is discharged, disassembled and the battery core is taken out; the battery core is sealed with an aluminum-plastic bag, the battery core is squeezed with a tablet press to squeeze out the remaining electrolyte, and the electrolyte is taken out by piercing a hole with a needle tube, and the electrolyte is taken out for testing through a Cambridge viscometer; the design principle of the Cambridge viscometer is mainly based on electromagnetic oscillation viscosity detection technology, and a magnetic suspension probe is used for viscosity measurement. Specifically, the electrolyte is placed in a beaker, and the sample temperature is controlled at 25°C for detection. The reading is read after the displayed value is stable. The viscosity b of the electrolyte in this embodiment is shown in Table 2.
[0084] Detection of c: that is, the percentage c of the thickness of the coating and the diaphragm in the diaphragm is tested. There are two test methods, including:
[0085] a. Use a micrometer to measure the thickness H1 of the diaphragm; use tape to remove the coating on the surface of the diaphragm and then use a micrometer to measure the thickness H2 of the base film. The coating thickness is (H2-H1) / n, where n=1 or 2;
[0086] b. Obtain SEM of the diaphragm cross section and measure the thickness of the coating and base film using a scanning electron microscope.
[0087] In this embodiment, a scanning electron microscope is used to measure the thickness of the coating and the base film, and the percentage c of the thickness of the coating and the diaphragm obtained is shown in Table 2.
[0088] Test 1 - Fast charging capability @10-80% SOC:
[0089] a. Charge the battery at a constant current of 0.33C to an upper voltage of 4.25V, then charge at a constant voltage until the cut-off current is less than or equal to 0.05C, and then discharge;
[0090] Repeat the above steps 3 times, and take the discharge capacity of the third time as the discharge capacity of the battery;
[0091] b: Based on the battery capacity in a, the battery is charged at 0.33C to 10% SOC; recorded as T0;
[0092] c: Then charge at 4C, 3.5C, 3.0C, 2.75C, 2.5C, 2.25C, 2.0C, 1.75C, 1.5C, 1.25C, 1C, and 0.33C to cut-off voltages of 3.95V, 3.97V, 3.985V, 3.996V, 4.005V, 4.015V, 4.025V, 4.045V, 4.067V, 4.091V, 4.11V, and 4.25V respectively. Record the time it takes for the battery to be charged to 80% SOC as T1. T1-T0 is the fast charging time in min.
[0093] Test 2 - Energy Density Test:
[0094] a: Charge the battery at a constant current of 0.33C to an upper voltage of 4.25V, then charge at a constant voltage until the cut-off current is less than or equal to 0.05C, and then discharge;
[0095] Repeat the above steps 3 times, and take the third discharge energy as the discharge energy E of the battery;
[0096] b: The battery weight M is obtained by weighing with an electronic balance;
[0097] c: Calculation of weight energy density: E / M, unit: Wh / Kg.
[0098] Test 3-Cycle life @ 25℃ test:
[0099] The lithium-ion battery was placed at 25°C for 120 min, charged at 0.5C constant current to a cut-off voltage of 4.25V, charged at constant voltage to a cut-off current ≤ 0.05C, and after being placed at rest for 10 min, discharged at 0.5C constant current to 2.5V; the above was one cycle, and the above steps were repeated until 80% SOH was reached, and the number of cycles was recorded.
[0100] The above test results are shown in Table 2 below.
[0101] Table 2
[0102] / a b c a*b / c Fast charging capability Energy density Cycle life Example 1 16.80% 3.68 11.11% 5.564 22.5 346.6 706 Example 3 12.40% 2.69 13.04% 2.557 17.0 340.3 1008 Example 5 11.10% 2.21 30.00% 0.818 14.8 334.4 1232 Example 7 11.10% 2.19 23.20% 1.048 16.8 335.0 1115 Example 8 16.00% 2.69 14.29% 3.013 19.0 341.0 780 Embodiment 11 15.00% 3.21 39.13% 1.231 17.0 338.0 916 Example 12 21.00% 1.51 38.89% 0.815 15.4 342.6 864 Comparative Example 1 30.00% 2.39 11.11% 6.453 25.0 352.1 415
[0103] Table 3
[0104]
[0105] Table 4
[0106]
[0107]
[0108] It can be seen from the data in Tables 2-4 that the present invention can effectively improve the negative electrode wetting and thus improve the fast charging performance under good battery energy density by comprehensively adjusting the silicon content a, electrolyte viscosity b and the percentage c of coating thickness / base film thickness, and by controlling the value of a*b / c within the range of 0.037-5.625. By comparing the data in Tables 2-4, especially comparing Examples 1 and 8 with other examples in Table 2, and comparing Example 10 with other examples in Table 4, it can be seen that when the value of a*b / c is further preferably 0.165-2.585, it achieves the purpose of better improving fast charging performance and cycle performance while taking into account the battery energy density.
[0109] When the value of a is further preferably 2%-16%, b is further preferably 2.1-2.8, and c is further preferably 13%-32%, it can not only effectively improve the fast charging performance, but also significantly improve the cycle performance, and the number of cycles can reach more than 1000.
[0110] When a, b, and c are all within the preferred range, and the values of a*b / c are all within the preferred range of 0.165-2.585, when the silicon-based material is a silicon-carbon material, the value of a*b / c is further preferably 0.431-1.05, and when the compaction density of the negative electrode sheet is 1.45-1.8 g / cm3, the value of a*b / c is further preferably 0.333-0.82; when the above-mentioned preferred setting conditions are met at the same time, referring to Examples 5 and 7 in Table 2, and Example 6 in Table 4, it can be seen from the comparison with the data of other embodiments that it improves the fast charging performance while significantly improving the cycle performance.
[0111] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A battery, comprising a battery cell and an electrolyte, wherein the battery cell comprises a negative electrode sheet and a separator, the negative electrode sheet comprises a current collector and a negative electrode active material layer, the negative electrode active material layer comprises a silicon-based material, and the separator comprises a base film and a coating; characterized in that: The mass percentage of silicon element in the negative electrode active material layer is a; the viscosity of the electrolyte is b, and the unit is cp; the percentage of the coating thickness to the diaphragm thickness is c; 0.037≤a*b / c≤5.
625.
2. The battery according to claim 1, characterized in that The a is 0.5%-30%; And / or, b is 1.5-3.7; And / or, said c is 8%-50%.
3. The battery according to claim 2, characterized in that The a is 2%-16%; And / or, b is 2.1-2.8; And / or, said c is 13%-32%.
4. The battery according to any one of claims 1 to 3, characterized in that: The value of a*b / c is 0.165-2.585; When the silicon-based material is a silicon-carbon material, the value of a*b / c is 0.431-1.
05.
5. The battery according to claim 1, characterized in that The compaction density of the negative electrode sheet is 1.25-1.8g / cm 3 .
6. The battery according to claim 5, characterized in that When the compaction density of the negative electrode is 1.45-1.8g / cm 3 When , the value of a*b / c is 0.333-0.
82.
7. The battery according to claim 1, characterized in that The electrolyte includes a solvent and a lithium salt; The solvent is selected from carbonates, carboxylates, ethers, sulfones, nitriles, phosphates or fluorides of the above solvents; The lithium salt is selected from lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium perchlorate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium trifluoromethanesulfonate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium difluorophosphate, lithium difluorobisoxalatophosphate and lithium tetrafluorooxalatophosphate.
8. The battery according to claim 7, characterized in that The solvent contains at least 10 wt% to 60 wt% of carbonate solvent and 0 wt% to 50 wt% of carboxylate solvent; And / or, the lithium salt concentration in the electrolyte is 0.8-2.5M.
9. The battery according to claim 1, characterized in that The coating contains an inorganic component, and the inorganic component contained in the coating is selected from alumina, boehmite, silica, zirconium oxide, titanium dioxide, cerium oxide and magnesium aluminate; The coating has a thickness of 1-7 μm.
10. An electrical device, characterized in that: A battery comprising any one of claims 1 to 9; the battery comprising a positive electrode sheet, wherein the positive electrode active material in the positive electrode sheet comprises LiNi x Co y Mn z O2, where 1>x≥0.5, x+y+z=1.
Citation Information
Cited By
Battery and electric device
WO2026097813A1
Battery cell, secondary battery, and electrical apparatus
WO2026179418A1
Lithium-ion battery cell, lithium-ion battery and electric device
WO2026184251A1